Talking Stick Learning Model to Optimize Interpersonal Intelligence of Children Aged 5-6 Years - Desy Dwi Rahmawati; Winda Sherly Utami; Sri Indriani Harianja (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
This study was motivated by the researcher’s observations, which showed that there were still several problems related to children’s interpersonal intelligence. The problem identified was that out of 18 children in group B3, 11 appeared to have a low level of interpersonal intelligence. This condition became the focus of further investigation because it could hinder their social and emotional development in the future. The purpose of this study was to determine the extent of the effect of the talking stick learning model on the interpersonal intelligence of children aged 5–6 years at TK Islam Al-Moestafa, Jambi City. The method used in this study was a pre-experimental design in the form of a one-group pretest-posttest design. The total population in this study consisted of 60 children. The research sample included 18 children from group B3, selected using purposive sampling technique. Data were collected through observation and documentation, with an observation sheet used as the validated research instrument. Data analysis was conducted using normality and homogeneity tests, followed by hypothesis testing using a paired samples t-test. The results of the t-test analysis showed a significance value of 0.001 < 0.05, which meant that there was a significant effect of the use of the talking stick learning model, providing a positive impact on the interpersonal intelligence of children aged 5–6 years at TK Islam Al-Moestafa, Jambi City. The effect size was 5.82, which fell into the strong effect category. Therefore, the talking stick learning model was effective in optimizing the interpersonal intelligence of children aged 5–6 years at TK Islam Al-Moestafa, Jambi City.